Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation